2008
DOI: 10.1111/j.1537-2995.2008.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatitis C virus infection among blood donors in Beijing and implications for improving the pretesting donor screening process

Abstract: Histories of blood transfusion before 1995, plasma donation, previous hepatitis infection, or elevated ALT were risk factors for HCV infection among blood donors in Beijing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…A study of 425 patients from a single hospital population reported genotypes 1 (14%), 1a (15%), 1b (23%), 2 (9%), 3 (31%), 4 (5%), 6 (2%) and mixed (1%) (27). The results were consistent with other work conducted by a national reference laboratory (26), which also showed that genotype 3 was more prevalent in younger age cohorts (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) year olds), indicative of transmission via IDU, and that genotype 1b was identified more frequently among patients with transfusion-acquired HCV (26).…”
Section: Genotype Distributionsupporting
confidence: 86%
See 1 more Smart Citation
“…A study of 425 patients from a single hospital population reported genotypes 1 (14%), 1a (15%), 1b (23%), 2 (9%), 3 (31%), 4 (5%), 6 (2%) and mixed (1%) (27). The results were consistent with other work conducted by a national reference laboratory (26), which also showed that genotype 3 was more prevalent in younger age cohorts (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) year olds), indicative of transmission via IDU, and that genotype 1b was identified more frequently among patients with transfusion-acquired HCV (26).…”
Section: Genotype Distributionsupporting
confidence: 86%
“…In children, the prevalence was reported between 0.1 and 0.9% (259,273). A general increase in prevalence with age was observed: 4.49% in o 15, 2.05% in [15][16][17][18][19][20][21][22][23][24]5.10% in [25][26][27][28][29][30][31][32][33][34]8.64% in 35-44, 15% in 45-54 and 11.9% in Z55 years old in a cohort of outpatient attendees and admitted patients (250). Others reported that prevalence was highest in males aged 4 40 years (6.2%) and in females 40-49 years (5.0%) (246).…”
Section: Risk Factorsmentioning
confidence: 99%
“…History of blood transfusion has consistently been reported to be associated with HCV infection among Chinese blood donors . A previous risk factor study in Beijing blood donors found that the majority (91.7%) of HCV cases had received transfusion before 1996 .…”
Section: Discussionmentioning
confidence: 39%
“…Few other studies also have shown an association of history of blood transfusion with an increased risk of polymerase chain reaction (PCR) positivity or confirmed HCV cases. [91011]…”
Section: Discussionmentioning
confidence: 99%